Naskah budi pekerti dalam naskah dolanan bocah - Ekowati, Venny Indria (Kejawen, 2015)
Javanese manuscript contains various kinds of result of Javanese society's, creativities, senses, and will during their time. One of them can be seen in the Naskah Dolanan Bocah manuscript which is collected by Sonobudoyo Muzium Yogyakarta. This manuscript contains 41 types of Javanese traditional games, complete with their rules and simple illustrations of the games. This traditional game is now becoming obsolete by the Javanese society. In fact there are at least eight moral values contained in those traditional games. Those values are: (1) Cooperation and Harmony, (2) Honesty, (3) Fair, (4) Sincere, (5) Compassion, (6) Patience, (7) Manners, and (8) Environment Care. Jianese traditional games in Dolanan Bocah manuscipt also combine cognitive, psychomotor, and affective elements as an integrated elements. The cognitive aspect is seen in the use of strategy and reasoning in the game. Psychomotor aspects seen on the movement and the songs performed during the game, and affective aspects towards character and behaviour established during the play of traditional games.